2022
DOI: 10.1016/j.jsxm.2022.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Rich Plasma (PRP) Growth Factor Concentration Varies in Men with Erectile Dysfunction

Abstract: Background Platelet Rich Plasma (PRP) is a novel therapy rich in growth factors and cytokines used to target the underlying causes of erectile dysfunction (ED). It is not known, however, if the composition of growth factors in PRP varies between men. Aim To evaluate PRP growth factor variability among men with ED. Methods Whole blood was collected from 8 part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Restorative therapies for erectile dysfunction have attracted significant interest and research attention within men’s health with multiple ongoing clinical trials and many unanswered questions [ 16 , 17 ]. A high prevalence of poor-quality information online poses a particular challenge to today’s urologists [ 16 , 17 ]. We theorized that AI may be able to efficiently assess and discern credible information among online text sources with similar efficacy as human reviewers.…”
Section: Discussionmentioning
confidence: 99%
“…Restorative therapies for erectile dysfunction have attracted significant interest and research attention within men’s health with multiple ongoing clinical trials and many unanswered questions [ 16 , 17 ]. A high prevalence of poor-quality information online poses a particular challenge to today’s urologists [ 16 , 17 ]. We theorized that AI may be able to efficiently assess and discern credible information among online text sources with similar efficacy as human reviewers.…”
Section: Discussionmentioning
confidence: 99%
“…Platelet-rich plasma (PRP) is widely noticed by researchers and clinicians because it is rich in a variety of growth factors and cytokines, such as insulin-like growth factor 1 (IGF-1), bFGF, EGF, VEGF, TGF-β, and PDGF ( Marques et al, 2015 ; Ziegler et al, 2019 ; Poulios et al, 2021 ; Khodamoradi et al, 2022 ). It has been reported that the injection of PRP could promote the proliferation of urothelial cells and the expression of cytoskeleton and urinary barrier function protein in the treatment of recurrent urinary tract infection ( Jiang et al, 2021 ).…”
Section: Biological Functionalization Strategiesmentioning
confidence: 99%
“…Moreover, given that autologous PRP is currently the most commonly utilized approach to administration, it should be noted that there is some recent data to suggest that growth factor concentration can vary among men with ED. 94 This data could suggest that not all patients may achieve the same benefits from their own PRP and that more research into what patient factors may potentiate or impair PRP response will also be important to optimize patient selection and treatment efficacy. A recent systematic review concluded that currently there is not enough data to suggest that PRP improves PD significantly enough to achieve easier sexual penetration.…”
Section: Novel Therapies For Peyronie’s Diseasementioning
confidence: 99%